Newly discovered Late Bronze Age settlement in the vicinity of Kamenovo, Kubrat municipality, northeastern Bulgariа: preliminary results - Petar Minkov; Zheni Vasileva; Denitsa Sandeva; Yana Dimitrova; Stanimira Taneva; Plamen Georgiev; Nikola Tonkov; Hristo Popov (Българско е-Списание за Археология)
This article presents the preliminary results of several consecutive studies conducted in the period 2021–2024. The area of the Ludogorsko Plateau is characterised by one of the highest concentrations of Late Bronze Age finds discovered in present-day Bulgaria. Unfortunately, more than 100 years after the first discoveries, no large-scale studies focusing on the period of the 2nd millenium BC have been carried out. The fieldwork strategy included combination of various research methods – from remote and non-destructive methods (LiDAR, geophysics, field surveys) to conventional archaeological excavations (trenches and long-term excavations over a larger area) for the sites selected for these studies.